2020
DOI: 10.1002/ajhb.23535
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive hormone measurement from minimally invasive sample types: Methodological considerations and anthropological importance

Abstract: Energetic investment in human reproduction has long been recognized as costly, influencing developmental, physiological, and behavioral patterns in males and females. These effects are largely coordinated through the actions of reproductive hormones (eg, testosterone, estradiol, and progesterone). Here, the utility and limitations of minimally invasive sampling techniques are explored, providing a novel perspective on how reproductive hormone measurements can enhance reproductive endocrinology research. Saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 177 publications
(307 reference statements)
0
9
0
Order By: Relevance
“…The authors found an average ALLO concentration of 4.4 ng/mL in gestational weeks 12 to 25 and of 7.6 ng/mL in gestational weeks 22 to 32 [ 30 ]. The concentrations of ALLO in saliva are expected to be much lower than concentrations in blood [ 21 ] and would therefore not fall into the linearity of the LC–MS method used. It may be possible that a more sensitive LC–MS system would yield better results; this should be tested further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found an average ALLO concentration of 4.4 ng/mL in gestational weeks 12 to 25 and of 7.6 ng/mL in gestational weeks 22 to 32 [ 30 ]. The concentrations of ALLO in saliva are expected to be much lower than concentrations in blood [ 21 ] and would therefore not fall into the linearity of the LC–MS method used. It may be possible that a more sensitive LC–MS system would yield better results; this should be tested further.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, circulating ALLO concentrations rise dramatically, reaching a six-to-tenfold increase compared to non-pregnant luteal levels [ 10 , 18 , 19 ]. The elevated circulating hormone levels during pregnancy should improve the detectability of ALLO and, thus, facilitate its measurement in saliva [ 20 , 21 ]. A further challenge lies in the matrix composition of saliva and other biological fluids and its effects on analyte detection [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Part 1 of the special issue also showcased human biologists as leaders in the development of novel biomarkers obtained through minimally invasive methods such as finger prick capillary blood, saliva, urine, and hair, as well as in creating accessible summaries and guides for working with these tools, outlining the opportunities and challenges. The earlier special issue featured contributions from Gildner (2021) and Quinn (2021) that systematically reviewed and described the broad applicability of existing minimally invasive reproductive hormone methods and milk composition techniques, respectively. That same issue included Cepon‐Robins' (2021) timely review of autoimmune biomarkers, making the case for increased investment in the development of minimally invasive, field‐friendly methods that will allow the measurement of autoimmune and inflammatory disorders beyond the current situation in which their use is primarily limited to hospitals and clinics in wealthy nations.…”
Section: Introductionmentioning
confidence: 99%
“…Medical research has thoroughly examined many molecules that are suitable for the detection of cancer at a population level, despite presently being of limited use in clinical settings due to more stringent requirements for sensitivity and specificity. Uniting oncology with human biology, which is a leader in the development of minimally invasive techniques for population-based studies (Eick et al, 2016(Eick et al, , 2017(Eick et al, , 2019(Eick et al, , 2020Gildner, 2021;McDade, 2014;McDade et al, 2007McDade et al, , 2020Rej et al, 2021;Valeggia, 2007), provides an opportunity to apply well-researched methods to a field that has recognized the need for greater biomarker sampling and less invasive techniques.…”
Section: Introductionmentioning
confidence: 99%